Synergistic adsorption-electrocatalysis of carbon nanotubes/vanadium sulfide modified separator toward high performance Li–S batteries. (10th January 2023) - Yu, Changming; Jin, Qi; Zhang, Liyuan; Zhao, Kaixin; Zhang, Lirong; Han, Fengfeng; Yao, Jing; Lu, Huiqing; Zhang, Xitian; Wu, Lili
Highlights: A modified separator of MWCNT/VS2 for high-performance Li-S batteries is fabricated. MWCNT/VS2 -PP can promote the adsorption and redox kinetic of polysulfides. The MWCNT/VS2 -PP battery exhibited improved rate capability and cycling stability. The origin of MWCNT/VS2 -PP superior performance was revealed. Abstract: Lithium–sulfur (Li–S) batteries have attracted wide research attention due to their high energy density, abundant reserves, and low cost. However, the slow reaction kinetics and the shuttle effect of lithium polysulfides (LiPSs) lead to poor rate performance and cycling stability of Li–S batteries. To overcome both barriers, a multi-walled carbon nanotube (MWCNT)/vanadium sulfide (VS2 )-modified polypropylene (PP) separator (MWCNT/VS2 -PP) is prepared via a simple vacuum filtration method. Benefiting from good nucleation and surface diffusion (MWCNT) with effective anchoring capability and catalysis activity (VS2 ), MWCNT/VS2 can efficiently accelerate the electrochemical kinetics, promote the Li2 S nucleation, and depress the polysulfide shuttling. As a consequence, the Li–S batteries assembled with MWCNT/VS2 -PP exhibit a dramatically enhanced rate capacity (862.4 mAh g −1 at 5 C) and excellent cycling stability (727 mAh g −1 at 1 C after 500 cycles). This work introduces a feasible strategy to anchor polysulfides and accelerate kinetic process by developing modified separators with strong chemisorption and catalytic activity, demonstrating the great potential of MWCNT/VS2 -PP for outstanding rate performance and long cycling stability Li–S batteries. Graphical abstract: Image, graphical abstract